Uma vida inteira e todos os seus ciclos? - Souza, Abraão Golfet de (Universidade Federal de São Carlos, 2024)
This work presents a narrative report on the experience of a medical student throughout the course. The narrative, rich in details and reflections, follows the author from the early years of graduation to the completion of the internship. Through a qualitative approach, the study explores the various phases of medical training, from initial enthusiasm to the challenges of clinical practice. The report highlights the importance of humanization in medical practice, the search for a balance between technique and empathy, and the impact of the COVID-19 pandemic on the training of future health professionals. Throughout the narrative, the author reflects on the construction of professional identity, the importance of research, and the influence of mentors and colleagues. The keywords that best represent this work are: medical education, student experience, humanization, narrative report, professional trajectory, professional identity.
A whole life and all its cycles?
Keywords: Formação médica; Experiência do estudante; Humanização; Relato de experiência; Trajetória profissional; CIENCIAS DA SAUDE::MEDICINA